Combined catalytic oxidation and activated carbon adsorption of dioxins. Issue 2 (9th May 2014) - Ji, Shasha; Yu, Mingfeng; Ren, Yong; Buekens, Alfons; Lu, Shengyong; Cen, Kefa; Li, Xiaodong
Abstract : A mechanical mixture of lignite‐based activated carbon (AC) and V2 O5 ‐TiO2 ‐catalyst (CAT) is applied to destroy gas‐phase polychlorinated dibenzo‐p‐dioxins and dibenzofurans (PCDD/Fs) at high concentration (9.8 ng I‐TEQ Nm −3 ). Even at low temperature (160°C), the mix of AC/CAT shows high removal efficiency (RE) and destruction efficiency (DE). Varying the proportions of catalyst to AC has slight effect only on the DE‐value, but the RE‐value augments with rising ratio of AC, benefiting from enhanced adsorption on AC. When temperature is 160°C and the proportion of AC and CAT is 3:2, with oxygen concentration rising from 0 to 20%, the DE‐value even amplifies from 27 to 82%, by conversion of V 4+ OX into higher oxides. In the presence of ozone, PCDD/Fs are further broken down and the DE‐values of high‐chlorinated congeners surge. In the presence of ozone, AC breaks down to black brown flock, which contains more than 50 wt % carbons. Both reducing the content of AC and increasing the reaction temperature restrain the production of flock. The best condition occurred at 200°C in the presence of ozone with the DE of 98%, when the proportion of AC and CAT is 1:1. © 2014 American Institute of Chemical Engineers Environ Prog, 34: 346–350, 2015